Study of the Light Nuclei Cluster Structures in Three-Body Photodisintegration Reactions. Application for the Excited States of 6He Nucleus - N. Demekhina; H. Hakobyan; Zh. Manukyan; A. Sirunyan; H. Vartapetian
An experimental program for the study of cluster structures of excited states in the isotopes of He, Li and Be nuclei in three-body photo-disintegration processes is proposed. The investigations will be performed with 6Li, 7Li and 9Be targets in seven photo-disintegration reactions. As an application, the photo-disintegration of 7Li nuclei into the (t+t+p) final state with excitation and decay of neutron-rich 6He nucleus into the (t+t) channel is considered. The full Monte-Carlo simulation of the experiment is done with a special impact on the study of experimental setup performance, concerning the photon and excited states energy resolutions and efficiency. The experiment will be carried out at the bremsstrahlung photon beam of Yerevan Electron Synchrotron, working in stretcher mode at electron energy of 75 MeV.
Keywords: Physics; Nuclear physics